2006
DOI: 10.1139/x06-138
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of fire-plume properties simulated with the Fire Dynamics Simulator (FDS) and the Clark coupled wildfire model

Abstract: Before using a fluid dynamics physically based wildfire model to study wildfire, validation is necessary and model results need to be systematically and objectively analyzed and compared to real fires, which requires suitable data sets. Observational data from the Meteotron experiment are used to evaluate the fire-plume properties simulated by two fluid dynamics numerical wildfire models, the Fire Dynamics Simulator (FDS) and the Clark coupled atmosphere–fire model. Comparisons based on classical plume theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 19 publications
2
44
0
Order By: Relevance
“…In this respect, simulated updrafts appear in agreement with [45], who observed updraft values on the order of 20-30 m s −1 , and [46], who reported peaks of 32-60 m s −1 for crown fires occurring at the highest detectable heights (about 50 m). The largest simulated downward motion occurs in the upper plume behind the fire front (maximum of −7 m s −1 ), consistent with previous observations [47] and simulations [48]. (Figure 10d), which fall within the range of sensible heat fluxes as reported by [49].…”
Section: Dynamical Plume Structuresupporting
confidence: 91%
See 1 more Smart Citation
“…In this respect, simulated updrafts appear in agreement with [45], who observed updraft values on the order of 20-30 m s −1 , and [46], who reported peaks of 32-60 m s −1 for crown fires occurring at the highest detectable heights (about 50 m). The largest simulated downward motion occurs in the upper plume behind the fire front (maximum of −7 m s −1 ), consistent with previous observations [47] and simulations [48]. (Figure 10d), which fall within the range of sensible heat fluxes as reported by [49].…”
Section: Dynamical Plume Structuresupporting
confidence: 91%
“…The horizontal grid size is 2400 m for the outer domain covering 600 km × 720 km. The inner computational grids have grid increments of respectively 600, 200 and 50 m, covering a total area of respectively 144 km × 240 km, 48 …”
Section: Numerical Configurationmentioning
confidence: 99%
“…As mentioned above, coupled fire-atmosphere models [2,17,18] may provide an improvement to static fluid dynamic computations currently employed in operational front prediction software (for North American examples see [19,20]). Indeed, Large Eddy Simulations (LES) coupled with firebrand dispersal have shown that the fire plume may be quite different from the plume used in standard models like the Baum and McCaffery plume [21], leading to different firebrand trajectories [22][23][24]. In addition, there is an extensive literature covering empirical measurement of plume characteristics; extensive measurement of plume heights and characteristics in [25] compared a variety of plume models (different from Baum and McCaffery) against measurements for approximately 2000 wildfire plumes.…”
Section: The Havoc Caused By Spottingmentioning
confidence: 99%
“…Hence to determine the spotting distribution, we can apply the ignition operator to the total landed mass, where, as in the previous paragraph, the landing distribution's mass component is evaluated in terms of the inverse combustion operator at the landing time. The exact formula is given in Equation (23).…”
Section: L(x M)mentioning
confidence: 99%
See 1 more Smart Citation